Prototipe Aplikasi Komunikasi Menggunakan Jaringan Delay Tolerant Network Pada Perangkat Seluler Android - Slameta, Slameta; Ashari, Ashari; Rahmatullah, Griffani Megiyanto (LPPM POLITEKNIK LP3I BANDUNG, 2024)
In the current global context, the exchange of information through Internet networks has become increasingly vital, necessitating the effectiveness of communication technology. This is particularly true in areas with weak or unstable signal coverage such as intermittent areas. To address challenges such as frequent connection drops in these areas, Delay Tolerant Networking (DTN) architecture is offered as an alternative solution to overcome these problems. The conducted research aims to design and test a data communication application prototype using DTN architecture implemented on the Android operating system. The approach taken involves using the Analysis, Design, Development, Implementation, and Evaluation (ADDIE) method. In detail, the application is implemented on the Android operating system and integrates various routing protocols such as Epidemic, Spray and Wait, MaxProp, and ProphetV2 to optimize data transmission and reception under varying network conditions. Data collection techniques include measuring latency and data transfer speed in predetermined testing scenarios, while data analysis techniques involve evaluating the measurement results to determine the effectiveness of the routing protocols used. Evaluation is conducted and the results showing an average latency between 800-1400ms and speeds of 100-400kbps, depending on the distance and varying network conditions. This study validates the effectiveness of DTN in maintaining consistent communication in challenging network environments. The impact of this research on the advancement of informatics is to pave the way for further development and adaptation of DTN technology in various mobile applications and data networks.